Legal status of the cities of Galicyna in the nineteenth century (on the example of Stanislavov) - Ilyn L.; Kaleniuk O. (Науково-інформаційний вісник Івано-Франківського університету права імені Короля Данила Галицького)
Purpose. The purpose of our research is to specify the legal status of the cities and towns of Galicia during its stay as part of the Habsburg Empire. On the example of Stanislavov of the 19th century. show vectors of development of local self-government. Method. The methodology includes the complex use of a problem-chronological approach, the principles of historicism, objectivity, as well as general scientific, special legal and special historical methods. Results. It has been established that Magdeburg law is the basis of city self-government, but the Habsburg Empire is an example of effective reform and adaptation of legal norms to local needs. Stanislavov, who received Magdeburg law in 1662 and the processes that contributed to the transformation of legal norms that regulated the legal status of city authorities in the 19th century. is an ideal example for studying the system of local self-government. Moreover, such changes led to the socio-economic growth of the city, changes in the social structure of the population, and the introduction of new principles of self-government based on the norms of administrative law. The dynamics of the city's development proves that the time of functioning of the voivodeship and city government, which arose as a result of Magdeburg law, and the time of the existence of the burgomaster institute, which arose as a result of the administrative reform of 1866-1867, are significantly different. The main regulatory acts that regulated the activities of local self-government bodies and, in particular, the city administration in the second half of the 19th century. were the law «On Local Self-Government» (1862) and the «Regional Public Law» (1866). It has been established that it took almost a hundred years for the Austro-Hungarian authorities to change Magdeburg law to their own administrative law, which regulated the powers of local authorities. Scientific novelty. Based on the analysis of the legal norms of the Habsburg Empire, the scope of local self-government in Galicia is demonstrated using the example of Stanislavov. Practical significance. The results of the research can be used in further historical and legal studies, preparation of special courses.